Using intuitive awakening for business students to enhance strategic thinking skills - Prince, Melvin; Priporas, Constantinos (Australasian Marketing Journal (AMJ), 2018)
Keywords: dept.mkt; peer-reviewed

Industry Applications of Market Sensing Foreword to the Special Issue of Journal of Marketing and Management - Prince, Melvin; Priporas, Constantinos-Vasilios (Journal of Marketing and Management, 2014)
Keywords: Business And Economics--Management; Business And Economics--Marketing And Purchasing; Competition; Competitive advantage; Consumers; Knowledge management; Marketing; Product development; Product lines; Research; SWOT analysis; dept.mkt; ⛔ No DOI found

Continuties in Market Sensing - Prince, Melvin; Priporas, Constantinos-Vasilios (Market Sensing Today, 2015)
The concept and framework of market sensing was introduced by George Day more than 20 years ago into the strategic marketing literature and especially the philosophy of the market-driven organization. Market sensing can be considered an expression of a company's capabilities to scan the external environment. It does this by using real time data and intelligence to understand business or uncertain changes, to meet the current and future needs of the market, increase customer value, and outperform competitors. Market sensing enables managers to resist complacency, as well as to exploit opportunities and to design appropriate competitive strategies in order to remain successful in today's uncertain, rapidly changing, and hypercompetitive market. The present volume, Market Sensing Today, is essential reading in the marketing discipline, given the rapidly escalating innovative developments in market sensing techniques. This book of essays by acknowledged experts in the field fills an important knowledge gap and provides a realistic basis for strategy. It is replete with real-life examples of market sensing that illustrate actionable ideas for immediate impact that will improve organizational learning and accelerate growth. This book of contemporary tested and comprehensive concepts and methods grounded in diverse and rich experience is intended to stimulate creativity and insightful approaches for educators offering courses in strategy as well as for practitioners involved in crucial strategic decision making.
Keywords: Business & Economics / Marketing / General; Marketing research; dept.mkt; faculty_collection

Market Sensing Today - Prince, Melvin; Priporas, Constantinos-Vasilios (Business Expert Press, 2015)
Today's practicing marketers and scholars are confronted with a wide array of conflicting and imprecise information about best practices by which to search, gather, consolidate and interpret market information. Consequently, the need has never been greater to optimize market sensing to generate managerial actions that efficiently and effectively utilize knowledge of emerging consumer needs and competitive threats. This book addresses these urgent concerns. In essence, Market Sensing Today will cover, in ground-breaking ways, the following marketing managerial areas: * marketing opportunities associated with conventional and progressive bases of segmentation. * trends in market segment size and growth affecting long-range planning. * strategic direction for reaching future goals. * managerial understanding of assumptions competitors make about themselves. * the direction of current market strategies. * adding to the knowledge of a firm's core competencies. * how new market knowledge is best integrated into a firm's market intelligence system. * best ways to ensure the quality of information underlying decisions. * how benchmarking improves with market sensing. * best approaches for translating business issues into projects. * ways that key information may be disseminated within firms. * how proposed strategic changes are promoted by market sensing. * roles customer satisfaction insights play in policy. This book will address these key issues and more, to advance theory, research and practice based on latest developments in this vital field. It will show how to re-formulate traditional models that no longer work.
Keywords: dept.mrk; faculty_collection

Moral Disengagement, Machiavellianism and Academic Dishonesty - Prince, Melvin; Wang, J.; Priporas, Constantinos‐Vasilios (Journal of Academic Ethics, 2025)
Keywords: Academic Dishonesty; Academic dishonesty; Big Five personality traits; Cheating; Deviance; Dishonesty; Educational Research; Machiavellianism; Machiavellianism, Social Cognitive Theory; Moral Development; Moral Disengagement; Moral Philosophy and Applied Ethics; Moral Psychology; Moral disengagement; Morality; Personality; Psychology; Social psychology; Students; dept.mrk; peer-reviewed

The Diogenes Effect in retail buyer information processing - Prince, Melvin; Kwak, Lynn; Priporas, Constantinos Vasilios (Journal of Retailing and Consumer Services, 2019)
The search for an ethical vendor who is honest and trustworthy in the exchange process is conceptualized as the Diogenes Effect, an innovative concept. In the light of this effect, the theoretical framework of the current study's model involved retail buyer responses to vendor persuasive communications. The model was tested by having a sample of retailer buyers complete a survey of information processing in the search for a product and vendor. This study innovatively links vendor communication effects to retailer buyer decision-making and evaluations by incorporating and integrating elements of Elaboration Likelihood Theory. Contributing to theory-building, it was found that when retailer buyers searched for a vendor with an ethical orientation, the result was intensified central processing of information and decreased peripheral information processing. This was especially salient when retailer buyers had greater longevity of professional experience. The next stage, information processing, led to feedback that enabled assessment of vendor trustworthiness. Finally, the research measured the level of fulfillment in the post-purchase phase. In the end, typical outcomes included the generation of favorable expectations of vendor performance, as well as the positive impact of those heightened favorable expectations on greater satisfaction with the value ultimately received from the vendor.
Keywords: Diogenes; Diogenes effect; Elaboration likelihood model; Expectations; Information processing; Retailer buying decision; Satisfaction; decision making; dept.mkt; information processing; modeling; peer-reviewed; retailing

Uniting theory and empirical research: market sensing and marketing research - Prince, Melvin; Gabay, G; Priporas, Constantinos; Moskowitz, H (Quantitative research methods in consumer psychology: contemporary and data driven approaches, 2018)
Quantitative consumer research has long been the backbone of consumer psychology producing insights with peerless validity and reliability. This new book addresses a broad range of approaches to consumer psychology research along with developments in quantitative consumer research. Experts in their respective fields offer a perspective into this rapidly changing discipline of quantitative consumer research. The book focuses on new techniques as well as adaptations of traditional approaches and addresses ethics that relate to contemporary research approaches. The text is appropriate for use with university students at all academic levels. Each chapter provides both a theoretical grounding in its topic area and offers applied examples of the use of the approach in consumer settings. Exercises are provided at the end of each chapter to test student learning. Topics covered are quantitative research techniques, measurement theory and psychological scaling, mapping sentences for planning and managing research, using qualitative research to elucidate quantitative research findings, big data and its visualization, extracting insights from online data, modeling the consumer, social media and digital market analysis, connectionist modeling of consumer choice, market sensing and marketing research, preparing data for analysis;, and ethics. The book may be used on its own as a textbook and may also be used as a supplementary text in quantitative research courses.
Keywords: dept.mkt